2015
DOI: 10.1111/cge.12597
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for return of incidental findings from genome sequencing among women diagnosed with breast cancer at a young age

Abstract: While experts have made recommendations, information is needed regarding what genome sequencing results patients would like returned. We investigated what results women diagnosed with breast cancer at a young age would want returned and why. We conducted 60 semi-structured, in-person individual interviews with women diagnosed with breast cancer at age 40 or younger. We examined interest in six types of incidental findings and reasons for interest or disinterest in each type. Two coders independently coded inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…We recruited a purposive sample of 60 adult women from an existing nationwide cohort of women diagnosed with breast cancer at age 40 or younger, the Young Women’s Breast Cancer Program (YWBCP) (Kaphingst et al 2016). YWBCP participants in the St. Louis region were contacted by e-mail, letter, and e-newsletter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recruited a purposive sample of 60 adult women from an existing nationwide cohort of women diagnosed with breast cancer at age 40 or younger, the Young Women’s Breast Cancer Program (YWBCP) (Kaphingst et al 2016). YWBCP participants in the St. Louis region were contacted by e-mail, letter, and e-newsletter.…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment materials stated the purpose of the study (i.e., to learn more about how best to return genetic information to women who have been diagnosed with breast cancer at a young age) and expressed interest in participation from women with differing viewpoints, regardless of prior experience with genetic testing. Recruitment was stratified into four subgroups by family history of breast cancer, having received genetic testing, and BRCA1/2 mutation status, described in detail elsewhere (Kaphingst et al 2016). Recruitment was stratified so that we could explore differences among the participant subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that patients are generally positive about receiving unsolicited findings . This also holds true for cancer patients, but research suggests that patients become more cautious to receive all types of risk information when they are informed about the potential consequences for themselves and their family members . The possibility of encountering unsolicited findings makes clinical decision making in oncology even more complex, and a thoughtful disclosure policy is needed.…”
Section: Introductionmentioning
confidence: 99%
“…At the genome scale, we may expect a relatively high yield of findings per person because we can interrogate the majority of the exome or genome (Biesecker and Green 2014). Additionally, genome sequencing can provide information on incidental findings—conditions that would not impact a future child’s health, but that impact the patient directly such as mutations in BRCA1/2 that increase risk for hereditary breast and ovarian cancer (Green et al 2013; Kaphingst et al 2015; Regier et al 2015; Bennette et al 2013). Thus, carrier screening using genome sequencing (either whole genome or whole exome, which we will refer to as “genomic carrier screening”) could identify more mutations than panel screening and, as a result, identify more couples at risk of bearing children affected by genetic conditions.…”
Section: Introductionmentioning
confidence: 99%